Effectiveness and equity of vaccination strategies against Rift Valley fever in a heterogeneous landscape. - Warren S D Tennant; Eric Cardinale; Youssouf Moutroifi; Simon E F Spencer; Onzade Charafouddine; Michael J Tildesley; Raphaëlle Métras (PLoS Neglected Tropical Diseases)
Spatio-temporal variations in environmental and socio-agricultural factors create heterogeneity in livestock disease transmission risk, raising challenges in identifying populations most at risk and how this risk changes over time. Consequently, effective vaccination strategies require careful planning to achieve optimal or equitable outcomes across regions. We developed a metapopulation model for Rift Valley fever transmission in livestock across the Comoros archipelago which incorporates livestock vaccination in addition to heterogeneity in viral transmission rates and animal movements. We used the model to evaluate three vaccine allocation strategies-proportional allocation, optimal allocation for maximising total infections averted across the archipelago, and optimal allocation for more equitable outcomes across islands-under different vaccination coverage levels and animal identification scenarios. We report that (i) both archipelago-wide and island-specific strategy effectiveness were impacted by vaccination rate, allocation strategy, and animal identification approach, (ii) optimally allocating vaccines improved strategy effectiveness compared with proportional allocation but resulted in inequitable outcomes between islands, and (iii) tagging animals post-vaccination boosted overall strategy effectiveness for all vaccination rates.